62nd Meeting of the French Society of Neuropathology - Meeting Abstracts , December 4th. 2020 - French Society of Neuropathology, The (Free Neuropathology, 2020)
The French Society of Neuropathology was created in 1989, succeeding the French Club of Neuropathology set up in 1965. The Society organizes two scientific meetings per year.